Growth-Factor-Releasing Polyelectrolyte Multilayer Films to Control the Cell Culture Environment - Ding, Ivan (Langmuir : the ACS journal of surfaces and colloids, 2018)
Polyelectrolyte multilayers (PEMs) are of great interest as cell culture surfaces because of their ability to modify topography and surface energy and release biologically relevant molecules such as growth factors. In this work, fibroblast growth factor 2 (FGF2) was adsorbed directly onto polystyrene, plasma-treated polystyrene, and glass surfaces with a poly(methacrylic acid) and poly-l-histidine PEM assembled above it. Up to 14 ng/cm2 of FGF2 could be released from plasma-treated polystyrene surfaces over the course of 7 days with an FGF2 solution concentration of 100 μg/mL applied during the adsorption process. This release rate could be modulated by adjusting the adsorption concentration, decreasing to as low as 2 ng/cm2 total release over 7 days using a 12.5 μg/mL FGF2 solution. The surface energy and roughness could also be regulated using the adsorbed PEM. These properties were found to be substrate- and first-layer-dependent, supporting current theories of PEM assembly. When released, FGF2 from the PEMs was found to significantly enhance fibroblast proliferation as compared to culture conditions without FGF2. The results showed that growth factor release profiles and surface properties are easily controllable through modification of the PEM assembly steps and that these strategies can be effectively applied to common cell culture surfaces to control the cell fate